Dystocia due to Dicephalus dipus tetrabrachius ischiopagus conjoined monster in a she buffalo - SHUKLA, S P; PANDEY, S S (The Indian Journal of Animal Reproduction, 2005)
A rare case of Dicephalus Dipus Tetrabrachius Ischiopagus Conjoined moster case in a she buffalo is being reported here.
Keywords: Dicephalus dipus tetrabrachius ischioopagus conjoined monster; she buffalo